2005
DOI: 10.1111/j.1365-2230.2005.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive multifocal Buruli ulcer with associated osteomyelitis in an HIV-positive patient

Abstract: Mycobacterium ulcerans infection causes a skin disease known as Buruli ulcer (BU), a disorder manifested usually as a solitary and painless nodule or papule that progresses to massive necrotizing destruction and cutaneous ulceration. When healing occurs, it often results in disabling deformities. Buruli ulcer is considered the third most common mycobacterial disease in immunocompetent people, after tuberculosis and leprosy. Although the emergence of Buruli ulcer in Western African countries over the past decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…After completion of treatment, AFB throughout the whole footpad revealed a beaded structure, and cultures went negative, supporting the hypothesis of beading as a marker for loss of viability. Osteomyelitis is a major severe complication occurring in Ͼ10% of all BU patients (31,39). We observed in 15% of all mouse footpads examined bacterial infiltration in the bone marrow (data not shown), but with antibiotic treatment, these bacteria had a beaded appearance, indicating effective treatment.…”
Section: Discussionmentioning
confidence: 90%
“…After completion of treatment, AFB throughout the whole footpad revealed a beaded structure, and cultures went negative, supporting the hypothesis of beading as a marker for loss of viability. Osteomyelitis is a major severe complication occurring in Ͼ10% of all BU patients (31,39). We observed in 15% of all mouse footpads examined bacterial infiltration in the bone marrow (data not shown), but with antibiotic treatment, these bacteria had a beaded appearance, indicating effective treatment.…”
Section: Discussionmentioning
confidence: 90%
“…The rare published cases of disseminated forms of BU are often associated with bone involvement 1,2,5,8,9 and/or HIV co-infection. 7,8 The first large series of BU with laboratory-confirmed bone involvement focused on 73 cases from 18 months to 45 years of age with a median age of 14.5 years. 2 Thirty out of the 73 selected cases had a multifocal form at admission.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The multifocal forms, though rarely described in the literature, have been associated with osteomyelitis and human immunodeficiency virus (HIV) coinfection. 1,2,[5][6][7][8][9] However, the dissemination process behind these forms is not fully understood. Here, we present the case of a young boy who was admitted to the hospital with a bifocal form of BU that disseminated during treatment, generating several new foci.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study conducted in Cameroon revealed that human immunodeficiency virus (HIV) infection may affect the clinical presentation and severity of BU disease with a reported increased incidence of multiple, larger, and ulcerated BU lesions. [16][17][18] Data available on the absorption of antituberculosis medications in tuberculosis (TB)/HIV coinfection compared with HIV-negative patients showed conflicting results. 19,20 Therefore, whether antimycobacterial combination treatment is less efficacious in persons with HIV infection is unknown and needs to be systematically studied.…”
Section: Introductionmentioning
confidence: 99%